Using the Cooperative Board Game Pandemic to Study Teamwork. (September 2016) - Anania, Emily C.; Keebler, Joseph R.; Anglin, Katlin M.; Kring, Jason P.
Teamwork is paramount in most modern-day career fields. It is important for Human Factors students and professionals to understand the knowledge, skills, and attitudes (KSAs) requisite for excellent teamwork and to grasp the many hurdles that exist in appropriately measuring its major constructs. Although theories can be imparted didactically, and ideas for measurement discussed, conducting team-based research continues to be extremely difficult, in particular for measuring team behaviors. This paper discusses a potential remedy to this issue through the team-based game "Pandemic©." For this game, players work together on teams of 2-4 individuals with the goal of curing a set of 4 diseases that are eradicating humanity. Pandemic forces individuals to be resourceful and work together - and exemplifies many of the behavioral, attitudinal and cognitive components of teamwork. This paper discusses: a) the KSAs, team processes, and measurable outcomes that can be studied through Pandemic, b) aspects of the environment in Pandemic that can be manipulated, and c) an example of a study currently underway using Pandemic.